Halal products recognition using RFID/NFC technology - Khosravi, Mohsen; Muhammad Yusof, Zulkefli; Shah, Asadullah; Karbasi, Mostafa; Imtiaz Ali, Najma; Koondhar, M.Y. (Science International, 2017)
The current research is concentrated on approving the halal capacity for alinment aftermath by applying Radio Frequency Identification (RFID) or Near Filed Communication (NFC) automation to increase alive approaches in Malaysia. In the current delving, a cogent manner to analyses and attest the food character is adduced. Along with, developing a database of halal crops, halal cognizance and verification application in order to use in android smart phones are discussed. Research on up to date technologies to inset an RFID planted recognition order applying prevalent smart phones and estimation of other procedures to find out the appropriate system is balded.